Investigations into Transition-Metal-Catalyzed Arene Trifluoromethylation Reactions - Ye, Yingda; Sanford, Melanie S. (Synlett, 2012)
Trifluoromethyl-substituted arenes and heteroarenes are widely prevalent in pharmaceuticals and agrochemicals. As a result, the development of practical methods for the formation of aryl–CF3 bonds has become an active field of research. Over the past five years, transition-metal-catalyzed cross-coupling between aryl–X (X = halide, organometallic, or H) and various ‘CF3’ reagents has emerged as a particularly attractive approach to generating aryl–CF3 bonds. Despite many recent advances in this area, current methods generally suffer from limitations such as poor generality, harsh reaction conditions, the requirement for stoichiometric quantities of metals, and/or the use of costly CF3 sources. This Account describes our recent efforts to address some of these challenges by: (1) developing aryltrifluoromethylation reactions involving high oxidation state Pd intermediates, (2) exploiting AgCF3 for C–H trifluoromethylation, and (3) achieving Cu-catalyzed trifluoromethylation with photogenerated CF3•.1 Introduction2 Part 1. Aryltrifluoromethylation via High-Valent Palladium3 Part 2. Aryltrifluoromethylation Using AgCF34 Part 3. Cu-Catalyzed Aryltrifluoromethylation with CF3•5 Outlook
Keywords: trifluoromethylation; cross-coupling; palladium; silver; photocatalysis